An Observational Study of Vataja Hridroga in Correlation with Electrocardiographic Changes (AYUSHDHARA, 2023)
Diagnosing a disease is far important before initiating the treatment. Different important and involuntary functions are regulated by different Dosha, Dhatu and Oja, which are situated in the heart. Hridroga is disease of Marma and is life threatening. However emphasis is given to explore the possibility of inclusion of electrocardiogram a bedside investigating tool as a support to existing Pramanas and Rugna pariksha. In accordance with the World Health Organization, India accounts for one-fifth of these deaths worldwide especially in younger population. So the study aimed at comprehension of electrocardiographic changes in patients suffering from Vataja Hridroga as mentioned in Charak samhita, Sushruta Samhita, Ashtanghridaya and their specific correlation. 100 patients were included in the study and their symptomatology with electrocardiographic changes was observed. Vata Pradhan Kapha-Pitta Anubandha observed in in 38% patients, Vata Pradhan Kapha Anubandha observed in 34% patients, Keval Vata Pradhanata observed in 23% patients, Vata Pradhan Pitta Anubandha observed in 5% patients. This Kapha-Pitta Anubandha indicates its contribution in Srotorodha Pradhan and Avaranatmak Samprapti. Dosha vitiation and Anubandha causes various pathological changes in Hridaya like Shotha, Paka, Srotorodh thereby leads to specific changes in electrocardiogram. Significant correlation between two were observed.